Molecular mechanisms affecting estrogen receptor levels in breast cancer - Okat, Zehra (Journal of Surgery and Medicine, 2018)
The initiation of breast cancer, estrogen and its receptor (ER) perform significant functions. ER has two dissimilar forms, and they are commonly called as ER-alpha (-α) and ER-beta (-β). ERs are transcription factors. Expressions of ER-alpha (-α) protein are mainly arranged by the pathway of ubiquitin-proteasome. The hormone-responsive gene expression modulated by ER-α in addition to other nuclear receptors is a complicated process, which involves various cellular responses. And also, ER-α levels are related with the pathology and etiology of breast cancer. In this review which is about the transcription and expression of the ER-α gene may provide the find out biochemical mechanisms behind the breast carcinogenesis. The regulation of ER expression, histone-modifying enzymes, Progesterone receptor (PR), peroxisome proliferator-activated receptors (PPAR), hydrocarbon receptor (AhR), Glucocorticoid receptor (GR), hypoxia and lysine residuals in ER region described in detail in this work. Increasing the number of these studies, are very significant for developing new methods of estrogen-dependent cancers.